Causas de la baja visión en los niños: revisión sistemática (2023)
Objective: To identify the ocular pathologies that are reported as causes of low vision in children. Material and methods: The systematic search was carried out in Medline (PubMed), Embase and Lilacs. Observational studies with populations between 0-18 years of age, reporting visual acuity data between 20/60-20/400 and reporting the frequency of ocular pathologies were selected. Studies in which the diagnosis of the condition had not been verified by a professional, or which covered only cases of blindness, uncorrected refractive errors, or amblyopia, were excluded. The methodological quality of the articles was evaluated using the Joanna Briggs Institute instrument for prevalence studies. Results: 27 studies conducted in Asia (13 publications), Africa (6 studies), Oceania (4 studies), Europe and South America (2 studies each) were included. The most reported causes of low vision were: cataract, with prevalence between 0.8% and 27.2%; albinism with from 1.1% to 47%; nystagmus, with prevalence between 1.3% and 22%; retinal dystrophies between 3.5% and 50%; retinopathy of prematurity (ROP) with prevalence between 1.1% and 65.8%, optic atrophy between 0.2% and 17.6%, and glaucoma from 2.4% to 18.1%. Conclusions: Cataract, albinism and nystagmus are the ocular pathologies most mentioned by studies as a cause of low vision in children, as well as retinal diseases such as ROP and optic nerve diseases such as atrophy. However, there are numerous eye conditions that can result in low vision in the pediatric population.